Estrone Sulfate: Production Rate and Metabolism in Man - Ruder, Henry J. (1972)
Since estrone sulfate (E(1)S) is present at high concentration in plasma, we have examined the parameters of the plasma estrone, estradiol, E(1)S system. The metabolic clearance rate of E(1)S was 157 liter/day (range 70-292) in men and women. Estimated plasma production rates of E(1)S were (μgrams per day): men, 77; women, early follicular phase, 95; women, early luteal phase, 182. The conversion of plasma estrone and estradiol to E(1)S was measured and from these data and the metabolic clearance rates of the estrogens, the transfer factors were ρ(E)(1)(E)(1)(S) = 0.54 and ρ(E)(2)(E)(1)(S) = 0.65. Using average production rates, all plasma E(1)S could be shown to be derived from plasma estrone and estradiol. The conversion of plasma E(1)S to plasma estrone and estradiol was studied. The calculated transfer factors were: ρ(E)(1)(SE)(1) = 0.21, ρ(E)(1)(SE)(2) = 0.014. Essentially, similar data were obtained when E(1)S was given by mouth to two subjects. We conclude: (a) E(1)S is a major circulating plasma estrogen and has a long plasma half-life; (b) the large contributions of estrone and estradiol to plasma E(1)S are more than sufficient to account for all the circulating plasma E(1)S.